2022
DOI: 10.3390/biom12050714
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Iron Deposition in Neurodegeneration

Abstract: Disruption of cerebral iron regulation appears to have a role in aging and in the pathogenesis of various neurodegenerative disorders. Possible unfavorable impacts of iron accumulation include reactive oxygen species generation, induction of ferroptosis, and acceleration of inflammatory changes. Whole-brain iron-sensitive magnetic resonance imaging (MRI) techniques allow the examination of macroscopic patterns of brain iron deposits in vivo, while modern analytical methods ex vivo enable the determination of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 395 publications
0
54
0
1
Order By: Relevance
“…Thus, GLB1 has been suggested as an NBIA gene [ 49 ], although this depends on the authors. Single cases with NBIA phenotype have been reported for several genes such as REPS1 or CRAT [ 50 ], and in occasions, they are described as NBIA genes [ 51 ], or as genes to be considered NBIA genes if additional cases are reported [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GLB1 has been suggested as an NBIA gene [ 49 ], although this depends on the authors. Single cases with NBIA phenotype have been reported for several genes such as REPS1 or CRAT [ 50 ], and in occasions, they are described as NBIA genes [ 51 ], or as genes to be considered NBIA genes if additional cases are reported [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Fe, ferritin and total and HDL-cholesterol were all inversely related to AD severity and were shown by the Reactome database analysis to be involved in the subpathway of small molecules and vesicle-mediated transport and to converge towards an overactivation of scavenger receptors (SRs). SRs consist of a broad family of multifunctional proteins found on the membrane of a variety of cells, including microglial cells, involved in the binding and clearance of toxic ligands [ 48 , 49 ]. This altered signal could be indicative of an increased molecule trafficking during the neuroinflammation progression [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, based on postmortem analyses, individuals with A plaques and large Fe deposits are highly likely to develop dementia [ 56 ], possibly implicating that a tendency towards brain Fe accumulation could be a factor increasing AD susceptibility. In addition, during the onset of AD, microglial cells are believed to protect the brain by incorporating extracellular A filaments that are prone to bind several metals, such as Cu, Zn and Fe [ 49 , 57 ], until their maximum buffering capacity [ 57 ]. In this way, across years, Fe ions could increase and accumulate within the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron combined with mitochondrial oxidative stress can cause microglia to undergo ferroptosis, an iron-dependent programmed cell death ( 71 , 72 ), or induce ferroptosis in other cells via iron dysregulation or NO release ( 73 , 74 ). Recent research from our laboratory demonstrated that iron induces ROS production in microglia and amplifies ROS of stimulated microglia ( 75 ).…”
Section: Mechanisms Of Microglial Reactive Oxygen Species Generationmentioning
confidence: 99%